A restricted flooding mechanism for efficient anycast server localization in MANETs - Kostin, Alexander; Oz, Gurcu; Haci, Huseyin (Springer, 2015)
In wireless networks, reducing the number of redundant packets is one of the important mechanisms to minimize the required network bandwidth and the power consumed by network nodes. In this paper, an efficient and stateless flooding mechanism for anycast routing in wireless mobile ad hoc networks is proposed. The mechanism uses the technique of expanding ring search to decrease the related message traffic. A model of this mechanism is described. Based on this model, an extensive simulation study, together with real field experiments, has been conducted to investigate the performance of the proposed mechanism for anycast server localization. The simulation model has been developed in terms of a class of extended Petri nets that provide the possibility to conveniently represent parallelism of events and processes in the network. In simulation and real work experiments, fundamental performance metrics-response ratio, relative traffic and average response time-were investigated with varying distance of transmission and different combinations of model parameters. The obtained results show that the proposed approach to server localization in mobile ad hoc networks has good characteristics. As was demonstrated with a prototype system, the proposed routing method can be easily implemented at the application layer, without any changes at lower layers of the network protocol stack.
Keywords: Wireless ad hoc networks; Anycast routing; Restricted flooding; Expanded ring search